IPO Underpricing and Performance by Private Equity-Backed Entities in Nordic Countries 2005–2020 - Rinne, Ursula (2024)
The purpose of the study is to explore the underpricing of Initial Public Offerings (IPO) made by private equity-backed entities and their post-IPO performance in the Nordic region from 2005-2020. This study focuses on understanding the pre-listing ownership effect on underpricing and the post-IPO performance, answering the following questions: (1) How does underpricing occur in PE-backed IPOs compared to non-sponsored IPOs? (2) How do PE-backed IPOs perform post-IPO compared to non-sponsored IPOs? and (3) How do VC-backed IPOs perform post-IPO compared to BO-backed IPOs? The results of the study show that neither private equity backing nor offer size significantly explains underpricing or 3-year performance. IPOs have been a popular topic among researchers for decades, with IPO underpricing and long-term underperformance being well-documented anomalies. Despite the extensive prior literature on these anomalies, there is a notable lack of research on how pre-IPO ownership affects IPO performance. This study is motivated by the lack of research on sponsored and non-sponsored IPOs in the Nordic region. Additionally, only a few previous studies have categorized IPOs based on buyouts, venture capital, and non-sponsored ownership, adding novelty to this research field. This study seeks to provide more evidence into these specific IPO categories within this context. This study uses a quantitative method, with data mainly collected from the Refinitiv database. Underpricing is analyzed using raw initial returns and market-adjusted initial returns. Post-IPO performance is measured using the wealth relative method. OMX Nordic 40 index is used as the benchmark index. The study shows that sponsored IPOs experience larger underpricing than non-sponsored IPOs, even though the difference is not statistically significant, contradicting previous literature. Post-IPO performance is superior for sponsored IPOs when initial returns are included, aligning with prior literature. Venture-backed IPOs outperform buyout-backed IPOs in terms of underpricing and post-IPO performance when initial returns are included, consistent with some previous research.